(untitled) (Al-Aasar, 2025)
Allah (SWT), created the whole universe and sent down the first man, Adam (A.S) on the earth to follow His revealed guidance. Adam (A.S) did the same as directed by the grace of Allah Almighty. His offspring obeyed him and act upon his advices on the path of Allah Almighty. Some of them violated his teachings and made the society worst to live. Allah Almighty sent a number of prophets to educate and guide them towards His path but after a certain time the society again fall in sin and disobedience. After the period of the last prophet, Hazrat Muhammad (SAW) and his companions, Religious scholars and Sufis did the same practice to guide mankind in the light of Quran and Sunah. In this research article, this will be elaborated that how the sufis paid their duties with responsibility for the betterment of a society from all aspects with reference to Tafseer Durr e Mansoor by Imam Siyuti (R.A).